Description of sucessional process at Benfica Settlement Project, Southeastern of State of Pará, Eastern Amazon - Coelho, Roberta de Fátima Rodrigues; Miranda, Izildinha Souza; Mitja, Danielle (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2012)
The objective of this study was to characterize the successional stages through the structure and floristic composition of secondary forests in the Project of Settlement PA-Benfica in the Southeast of Pará. Twenty-two areas were chosen according to age of abandonment, physiognomic characteristics and history of use. The areas were initially grouped into four intervals of different ages: 1 year, 5 to 11 years, 12 to 15 years, 20 years and forest fragments that were a little disturbed by human activities. At each area a transect of 10 x 50 m was established, and all individuals were inventoried for the three strata: Upper stratum (DBH ≥ 10 cm), Medium stratum (DBH < 10 cm and height ≥ 2 m), and Lower stratum (height < 2 m). Over these 22 studied areas, were registered 637 species, 284 genera and 82 families. In all stratum the number of forest species were predominant compared to the number of pioneer species. The tree prevailed in all stratum, followed by shrubs and lianas. The density of pioneer species showed a decreasing trend in the first three successional stages. The structural parameters analyzed in this study showed no statistical differences between the successional stages.